MODELING OF SONGA - WAYAUA GEOTHERMAL SYSTEM BASED ON 3G DATA (GEOLOGY, GEOCHEMICAL, AND - Nandiwardhana, Damar
In the area of Songa - Wayaua, Bacan, North Maluku, indicated the existence of geothermal potential, shown by the emergence of surface manifestations such as fumaroles, hot springs, mud pools, steam ground, and alteration rocks. These manifestations are located in Songa and Wayaua Village with temperatures between 30° C - 98o C and pH 3 - 8. Their appearance are mostly in the volcanic environment (around Pele and Lansa Volcanoes), and manifestation water dominated by the chloride water type. In this research, mapping of surface geology structure and modeling geothermal system Songa - Wayaua, using 3G data (geology, geochemistry, geophysics) has been done. The result of mapping and modeling is expected to give description of geothermal system in the research area along with geothermal potentials and drilling exploration recommendations. Based on the results of 3G data analysis (geology, geochemistry, geophysics), the fault structures in the research area has a dominant direction of northwest - southeast and northeast - southwest. The morphology of the study area consists of hills, volcanic cones and aluvial plains. The geology of the study area comprised of quarterly - tertiary volcanic products from Jare, Amasing, Songa, Pele, Lansa, and Bibinoi Volcanoes then limestone units, Tawa granite rock units, and metamorphic rock units, that have tertiary age. The heat source is estimated to be located between Pele and Lansa Volcanoes. From results of magnetic studies, the area of low magnetic anomaly values around Pele and Lansa Volcanoes is estimated to be the area of heat accumulation on the surface. Based on the magnetotelluric investigation, the layers of the caps rock have a thickness between 500 - 900 m and the reservoir rock layer has a thickness between 900 - 1200 m. The reservoir temperature is estimated to be around 240 - 250° C (high enthalpy) with estimated reservoir zone of 15.5 km2, and geothermal potential about 143 Mwe.